Xanthones and Triterpenoids from Mesua daphnifolia and Garcinia maingayi - , G.C.L, Ee; , C.K, Lim; Y.L, Cheow,; M.A, Sukari (Malaysian Journal of Science, 2005)
Ananixanthone and two triterpenoids, lup-20(29)-en-3β-01 and friedelin were isolated from the stem bark extracts of Mesua daphnifolia. Meanwhile, chemical studies on the stem bark extracts of Garcinia maingayi yielded 1,3,7-trihydroxy-2-(3-methylbut-2-enyl)-xanthone and a triterpene, stigmasterol. Their structures were derived based on spectroscopic evidence, mainly ID and 2D NMR spectroscopy. All the crude extracts obtained were bioassayed against the larvae of Aedes aegypti. It was found that the crude hexane and chloroform extracts of Mesua daphnifolia were strongly active against the larvae with LC₅₀ value of as low as 9.7 and 6.0 ppm respectively.